2022
DOI: 10.1186/s12870-022-03948-4
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonic acid contributes to rice resistance against Magnaporthe oryzae

Abstract: Background The annual yield losses caused by the Rice Blast Fungus, Magnaporthe oryzae, range to the equivalent for feeding 60 million people. To ward off infection by this fungus, rice has evolved a generic basal immunity (so called compatible interaction), which acts in concert with strain-specific defence (so-called incompatible interaction). The plant-defence hormone jasmonic acid (JA) promotes the resistance to M. oryzae, but the underlying mechanisms remain elusive. To get more insight in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 73 publications
2
6
0
Order By: Relevance
“…In conclusion, the results from this study systematically showed that the JA signaling pathway modulates tea plant defenses against C. camelliae infection via the CsJAZ1/CsMYC2.2 module, thereby activating the downstream CsGSTU45 gene to promote the accumulation of H 2 O 2 (Figure 10). Besides, we found that JA signaling pathway plays a positive role in disease resistance against D. segeticola that causes leaf spot by increasing the content of H 2 O 2 (Figure S3), which conforms to the general opinion that JA signaling pathway positively regulates resistance against pathogens (Kazan & Manners, 2013;Ma et al, 2022;Shu et al, 2020;Wang et al, 2023). Besides, the expression level of CsGSTU45 in tea plant leaves inoculated with D. segeticola was significantly decreased after MeJA treatment at 24, 48, and 72 hpi (Figure S3d), indicating that the expression pattern of CsGSTU45 gene in the resistance against D. segeticola was different from that in the resistance against C. camelliae (Figure 4d).…”
Section: Csjaz1 Degradation In Response To Ja Treatmentsupporting
confidence: 87%
“…In conclusion, the results from this study systematically showed that the JA signaling pathway modulates tea plant defenses against C. camelliae infection via the CsJAZ1/CsMYC2.2 module, thereby activating the downstream CsGSTU45 gene to promote the accumulation of H 2 O 2 (Figure 10). Besides, we found that JA signaling pathway plays a positive role in disease resistance against D. segeticola that causes leaf spot by increasing the content of H 2 O 2 (Figure S3), which conforms to the general opinion that JA signaling pathway positively regulates resistance against pathogens (Kazan & Manners, 2013;Ma et al, 2022;Shu et al, 2020;Wang et al, 2023). Besides, the expression level of CsGSTU45 in tea plant leaves inoculated with D. segeticola was significantly decreased after MeJA treatment at 24, 48, and 72 hpi (Figure S3d), indicating that the expression pattern of CsGSTU45 gene in the resistance against D. segeticola was different from that in the resistance against C. camelliae (Figure 4d).…”
Section: Csjaz1 Degradation In Response To Ja Treatmentsupporting
confidence: 87%
“…Compared to lipoxygenase and AOS, the pattern for allene oxide cyclase (AOC) does not contrast as clearly between A. hypochondriacus × hybridus and A. caudatus ( Figure 5 C). This is consistent with the published record, where the prolonged activation of the jasmonate pathway in response to abiotic [ 85 ] and biotic [ 86 ] stress factors was brought about by the induction of AOS as a key enzyme rather than by stimulation of its downstream partner AOC.…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, within the hormone signaling‐related proteins, we identified JMT and four genes linked to JA biosynthesis, including LOX, AOS, and OPR. Several studies have demonstrated that both exogenous JA treatments and the overexpression of JA biosynthesis‐related genes enhance resistance against M. oryzae (Mei et al, 2006; Riemann et al, 2013; Ma et al, 2022). Additionally, a previous study highlighted that the activation of JMT expression leads to the production of methyl jasmonate, which serves as an intracellular regulator and a diffusible signal transducer in Arabidopsis (Seo et al, 2001).…”
Section: Discussionmentioning
confidence: 99%